The main clinical and immunological aspects of post-COVID syndrome - Makienko, Natalia; Minukhin, Valery; Kolyada, Tetyana; Toryanyk, Inna; Sklyar, anatoly (Annals of Mechnikov's Institute, 2022)
COVID-19 pandemic has encouraged many researchers to focus on the formation of further changes in the human body caused by SARS-CoV-2, as well as to study the epidemiological, pathophysiological and immunological processes of coronavirus disease in the long term in order to determine the therapeutic tactics of patients. The article presents the main overview provisions of the formation of post- Covid-19 syndrome in individuals who have been infected with SARS-CoV-2. The reasons, symptoms and the most common syndromes that occur in patients after suffering a coronavirus infection are also given. Scientific data obtained over the past months confirm that individuals after an infection show a clear relationship between the primary severity of the course and various reactions of immune system, changes in laboratory parameters to viral load in the remote period. The obtained research results indicate various immune reactions and basic syndromes that can persist for a long time, which, according to the authors, is associated not only with the presence of comorbid conditions in the patient, but also with the activation of endogenous viruses or an imbalance in the intestinal microbiota. Keywords: post- COVID -19 syndrome, clinical and immunological changes